Metabolism disruption induced by high ambient temperature - Ke Zhang; Gongbo Chen; Wan Liu; Jie He; Mengnan Pan; Zhongyang Chen; Jiahui Tong; Feifei Liu; Hao Xiang (Elsevier, 2024)
Background: Previous studies have assessed the cardiovascular risk attributable to high ambient temperature. However, the mechanisms underly acute cardiovascular responses associated with high ambient temperature remain incompletely understood. Objective: To identify acute cardiovascular responses associated with high temperature, and to understand the underlying mechanisms using metabolomics. Methods: We conducted a prospective panel study on young adults, organizing participants to undergo blood collection and temperature monitoring tautologically. Levels of 10 cardiovascular biomarkers and 4473 serum metabolites were measured. Levels of ambient temperature exposure were recorded by wearing personal monitors. We employed linear mixed-effect models to identify acute cardiovascular responses associated with ambient temperature, including differential biomarkers and metabolites. KEGG pathway analysis was performed on the differential metabolites to identify temperature-associated metabolic processes. Results: Exposure to elevated ambient temperature was associated with acute cardiovascular responses, including alterations in high-density lipoprotein, interleukin-6, C-reactive protein, diastolic pressure, and heart rate. These observed acute cardiovascular responses are probably attributed to metabolism disturbances, as 129 differential serum metabolites, accompanied by disruptions in 18 pathways, were identified. These differential metabolites and pathways primarily involve glycerophospholipid metabolism, which activates inflammation cytokines and subsequently induces adverse cardiovascular effects. Conclusions: Our findings suggest that elevated ambient temperature could potentially lead to cardiovascular responses among young adults in China. We propose that high ambient temperature exposure may contribute to acute cardiovascular effects by regulating the glycerophospholipid metabolism pathway.